Effectiveness Of Music Therapy On Post Operative Pain And Sleep Among Patients Who Undergone Abdominal Surgery (International Journal of Food and Nutritional Sciences, 2022)
Music therapy as a non pharmacological therapy can have multiple benefits including reduction of anxiety and pain, decreased heart rate, respiratory rate, myocardialoxygen demand, and systolic blood pressure and thus promote relaxation amonghospitalized patients. It is used widely all over the world as a painless, safe, inexpensive and practical nonpharmacologic therapeutic modality to reduce post operative pain. The present study aimed to evaluate the effectiveness of music therapy on post operative pain among patients who undergone abdominal surgery. The study setting was VMMC, Karaikal. Purposive sampling technique was used to select 100 patients who undergone abdominal surgeries for the study. The tool used for the data collection was self structured demographic profile and Visual Analogue Scale for assessing pain intensity. The result of the study revealed that the music therapy was effective in reducing the post operative pain among abdominal surgery patients from day 1 (t value 11.36) to day 2 (t value 8.61) and there was significant association found between level of pain and selected demographic variables such as age, type of surgery and duration of pain. The study concluded that Music therapy may help reduce pain and anxiety during painful procedures and thus increases patient satisfaction and overall procedure experience. Nurses must integrate non pharmacological therapies in management of pain.